Determinação do nível de controle econômico de Enneothrips flavens Moulton, 1941 (Thysanoptera: Thripidae) em cultivar de amendoim de porte ereto - Calore, R.a. [UNESP]; Boiça Júnior, A.l. [UNESP]; Chagas Filho, N.r.; Souza, J.r. De [UNESP] (Instituto Biológico, 2012)
The present work was aimed to evaluate different economic control levels of Enneothrips flavens in upright peanut plants, during the dry and wet seasons. The experiments were carried out at the Departamento de Fitossanidade, FCAV/UNESP - Jaboticabal, SP, Brazil, in 2007/2008. To evaluate the different E. flavens infestation levels, samplings were carried out at 17 days after plant emergence (DAE), collecting 10 closed leaflets per parcel. Peeled grain production (kg ha-1), and 100-seed dry mass (g) were also determined. Once the production and thiamethoxam + lambda-cyhalothrin spraying times were determined, the production gain (25 kg bags and kg.ha-1) and net profit variation were obtained. It was concluded that the peanut plants were more infested from 17 to 30 DAE and from 47 to 74 DAE for the dry cultivation and 32 to 53 DAE for the wet cultivation; the total-control treatment presented higher production and net profit variation as compared to the control plot with 26.43 bags.ha-1 and R$ 585.66 for the planting season held in drought, and 53.88 bags.ha-1 and R$ 1,354.26 for the planting done during the wet time; E. flavens control with 20% of leaflets attacked in both seasons was the closest to total control in the production (bags.ha-1) and net profit variation; the insecticide thiamethoxam + lambda-cyhalothrin was effective to control the pest, resulting in increased the peanut production in both cultivation seasons.

O objetivo do presente trabalho foi avaliar diferentes níveis de controle econômico de Enneothrips flavens, na cultura do amendoim ereto, nas épocas de cultivo das águas e da seca . O estudo foi realizado na área experimental do Departamento de Fitossanidade da FCAV/UNESP - Campus de Jaboticabal, SP, em 2007/2008. Para a avaliação, foram realizadas amostragens a partir dos 17 dias após a emergência das plantas (DAE), coletando-se dez folíolos fechados por parcela. Determinaram-se a produção de grãos em casca e a massa seca de 100 sementes. Determinadas a produção e o número de aplicações de thiametoxam + lambda-cialotrina, foram obtidos o ganho de produção e a variação no rendimento líquido. Concluiu-se no estudo que as plantas de amendoim foram mais infestadas dos 17 aos 30 e dos 47 aos 74 (DAE) para o plantio na época da seca e dos 32 aos 53 (DAE) na época das águas; o tratamento controle total obteve as maiores produções e variação no rendimento líquido em relação à testemunha com 26,43 sacas. ha-1 e R$ 585,66 para o plantio realizado na época da seca, e com 53,88 sacas. ha-1 e R$ 1354,26 para o plantio realizado na época das águas. O controle de E. flavens com 20% dos folíolos atacados para os cultivos rea-lizados foi o mais próximo do controle total na produção (sacas.ha-1) e variação do rendimento líquido; o inseticida thiametoxam + lambda-cialotrina mostrou-se eficiente no controle da praga resultando em acréscimo na produção de amendoim nas duas épocas de cultivo.
Determination of the level of economic control of Enneothrips flavens Moulton, 1941 (Thysanoptera: Thripidae) in the upright peanut crop
Keywords: Tripes; Arachis hypogaea L.; manejo integrado de pragas; Thrips; Arachis hypogaea L.; integrated pest management